Realisasi Kebijakan Bilingual Area Terhadap Punishment dan Reward - Ulfa febriyanti (Taqdir, 2021)
Bilingual area can’t be neglected to acquire language skills because it has considerable influence and roles. By that, This study aims to provide an example of bilingual area policies against punishment and reward at Daruttakwien Boarding School Bekasi. This study present the qualitative descriptive approach and observational studies design. The data for analysis consist of observation, interview, and document. The result indicate that bilingual area in this boarding school consists of several supporting activities such as trilingual speech and themed conversations every week. Punishment and reward have been implemented according to the portion. Punishment that given to language offenders is an educational punishment, and as a form of student motivation, rewards are given accordingly. Keywords: bilingual area, policy, punishment and reward